Artificial oocyte activation: evidence for clinical readiness. Issue 3 (March 2016) - Ebner, T.; Montag, M.
Abstract: Artificial oocyte activation using Ca 2+ ionophores or similar compounds is a widely applied technique in IVF laboratories. This is all the more interesting as most of the agents aiming for intracellular Ca 2+ increase do not result in physiological Ca 2+ oscillations but much rather cause a single Ca 2+ transient. Two observations from mammals may explain why a rather non-physiological single Ca 2+ peak caused by ionophores is sufficient to rescue cycles showing severe male factor infertility, deficient oocyte maturation, developmental problems in humans, or both. On the one hand, it has been shown that it is mainly the initial Ca 2+ rise that drives further downstream events, in particular calcium/calmodulin-dependent protein kinase II (CaMKII) action, and on the other, it is possible that this enzyme remains active even in the absence of Ca 2+ . It therefore seems that mammalian oocytes can respond to a wide range of intracellular Ca 2+ signals and have a surprisingly high degree of tolerance for changes in cytosolic Ca 2+ . As epigenetic consequences or differences in gene expression have not been studied to date, artificial oocyte activation has to be considered as experimental and should only be applied with a proper indication.